Modelling agglomeration and deposition of gas hydrates in industrial pipelines with combined CFD-PBM technique. (22nd October 2016) - Balakin, Boris V.; Lo, Simon; Kosinski, Pawel; Hoffmann, Alex C.
Abstract: Hydrates of light hydrocarbons are frequently formed during the subsea petroleum production. These crystalline ice-like solids may accumulate at concentrations sensitive from the flow assurance point of view, increasing the overall pumping costs and imposing sufficient risk of the pipe blockage. Modern trend in the assessment of hydrate-related risks is the development of numerical models of multiphase flows laden by hydrates. The present paper describes a computational fluid dynamic (CFD) model capable to simulate turbulent slurry of oil, water and gas hydrates. The population balance technique (PBM) coupled with CFD enables to predict such details of the process as the formation of hydrate phase, agglomeration of formed solids and granular interactions within the hydrate phase. The simulation results, validated with experimental data in terms of the slurry rheology, highlight flow patterns for a pipe system typical in oil industry. The model is in addition compared to the hydrate kinetics model from Colorado School of Mines (CSMHyK). Abstract : Highlights: The CFD-PBM model of the oil–water–hydrate slurry is developed. The model is validated with experimental data. The model is compared with CSMHyK from Colorado School of Mines. The flow patterns are described and analysed.